Africans and Europeans differ in their facial perception of dominance and sex-typicality: a multidimensional Bayesian approach - Fiala, Vojtěch; Tureček, Petr; Akoko, Robert Mbe; Pokorný, Šimon; Kleisner, Karel (Scientific reports, 2022)
Biosocial impact of facial dominance and sex-typicality is well-evidenced in various human groups. It remains unclear, though, whether perceived sex-typicality and dominance can be consistently predicted from sexually dimorphic facial features across populations. Using a combination of multidimensional Bayesian approach and geometric morphometrics, we explored associations between perceived dominance, perceived sex-typicality, measured sexual shape dimorphism, and skin colour in a European and an African population. Unlike previous studies, we investigated the effect of facial variation due to shape separately from variation due to visual cues not related to shape in natural nonmanipulated stimuli. In men, perceived masculinity was associated with perceived dominance in both populations. In European women higher perceived femininity was, surprisingly, likewise positively associated with perceived dominance. Both shape and non-shape components participate in the constitution of facial sex-typicality and dominance. Skin colour predicted perceived sex-typicality in Africans but not in Europeans. Members of each population probably use different cues to assess sex-typicality and dominance. Using our methods, we found no universal sexually dimorphic scale predicting human perception of sex-typicality and dominance. Unidimensional understanding of sex-typicality thus seems problematic and should be applied with cautions when studying perceived sex-typicality and its correlates.
Keywords: sexuální chování; obličej; Bayesova věta; lidé; percepce; Face; mužské pohlaví; Female; Male; Black People; Bayes Theorem; černoši; Perception; ženské pohlaví; Sexual Behavior; Humans